Evaluation and refinement of thermodynamic databases for mineral carbonation. (July 2018) - Voigt, Martin; Marieni, Chiara; Clark, Deirdre E.; Gíslason, Sigurður R.; Oelkers, Eric H.
Abstract: Thermodynamic models are often used to quantify fluid-rock interactions. The validity of such models critically depends on the accuracy of the thermodynamic database used. This study evaluated the quality of existing PHREEQC databases ( phreeqc.dat, llnl.dat, and core10.dat ) through the analysis of mineral saturation states for various carbonates, sulfur-containing minerals, silicates, and hydroxides. The comparison between data from available equilibrated dissolution-precipitation experiments and predicted saturation states reveals: i) systematic deviations when using phreeqc.dat at temperatures higher than ~ 90 °C; ii) a lack of direct solubility measurements of numerous sulfide and silicate minerals; iii) systematic solubility underestimates for kaolinite and brucite. To address these issues the carbfix.dat database was created based on the core10.dat database, revising several mineral solubilities and aqueous species stabilities to improve our ability to model fluid-rock interactions during basalt-hosted mineral carbonation efforts.